Analisis Keragaman Gen Laktoferin Pada Sapi Friesian-Holstein Dengan Metode Pcr-Rflp - Elmy Mariana (Jurnal Agripet, 2011)
Polymorphism analysis of lactoferrin gene on holstein-friesian cow with PCR-RFLP methodABSTRACT. The purposes of this study were to identify the polymorphism of the lactoferrin gene in Holstein-Friesian (HF) cows. The study was conducted on 281 heads of HF lactating cows coming from dairy farmers in Lembang district. Investigation on variant genotypes of the lactoferrin gene used PCR-RFLP method. Genotyping of the lactoferrin gene with EcoRI restriction enzyme produced two genotypes, i.e. AA (65.5%) and AB (34.5%) genotypes.